FORMATION OF CIVIL IDENTITY BY MEANS OF STUDENTS VISUAL ARTS: CULTURAL-HISTORICAL APPROACH - Melianat Bogatyreva (Вестник Северо-Кавказского федерального университета, 2022)
In the article there are six periods in the history of the formation of the Karachay-Balkar art and culture, the knowledge of which, according to the author, it is necessary in the creative leadership of artistic activities of the students and shaping their civic identity. There are three levels offormation of civil identity by means of fine art through the creation of collective and individual forms of involvement of children and adolescents folk arts in the process of art education.